Use of the Formal and Informal Financial Sectors: Does Gender Matter? Empirical Evidence from Rural Bangladesh - McKernan, Signe-Mary; Pitt, Mark M.; Moskowitz, David (World Bank, Washington, DC, 2012)
Access to transfers and credit, whether cash or in-kind, is a major source of poverty alleviation and income generation in many developing countries around the world. Women may especially benefit from transfers and credit in countries such as Bangladesh, where they often have few work alternatives. In this paper, the authors descriptively examine the formal and informal financial sectors of rural Bangladesh, placing special emphasis on differences between men and women. Their analysis uses unique data on the credit and transfer behaviors of 1,800 households in rural Bangladesh. The authors focus on five important questions: a) How important are the formal and informal financial sectors? b) What are the primary sources of gifts and loans within those sectors? c) Do men and women rely on different sources for finances (for example, formal versus informal) or different types of finances (for example, transfers versus loans)? d) How have the financial sectors evolved during the 1990s? e) What is the relationship between the formal and informal sectors?